Exploring shame as a relationally-conscious emotion - Çağın, Özlem. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
This study aimed at exploring shame by conceptualizing it as a relationally-conscious emotion. In a pilot study, prevalent shame-triggering themes among Turkish young people were identified and by using these themes as situational antecedents, a new scenario-based shame measure was constructed for the purposes of the study. In the main study, shame was examined in relation to expected reactions of other people in the shame-triggering contexts and to other emotions that might accompany shame. Participants consisted of 501 undergraduate students. In addition to the Shame Measure constructed for the study, The Guilt-Shame Measure, Interpersonal Sensitivity Measure, Interpersonal Problem Solving Inventory and Positive and Negative Affects Schedule were given to the participants to examine if there were individual differences in the responses. The results revealed that anxiety, tension and sadness accompanied shame in all situations except sexuality. In addition to these reactions, guilt and regret accompanied shame in moral transgressions and anger was seen together with shame in embarrassing public situations. A more pure shame was seen only in contexts associated with sexuality. In addition, specific reactions of others (e.g. contempt, disappointment) predicted the shame response depending on the nature of the context. Gender differences were observed with regard to sexuality and in the individual characteristics that significantly predicted the mean shame response. Overall, findings of the present study supported the theoretical perspectives that conceptualized shame as a relationally-conscious complex phenomenon with varying situational, affective and behavioral correlates.
Keywords: Shame.; Emotions.